Economic burden of influenza illness among children under 5 years in Suzhou, China: Report from the cost surveys during 2011/12 to 2016/17 influenza seasons. Issue 8 (22nd February 2021) - Wang, Yin; Chen, Liling; Cheng, Fangfang; Biggerstaff, Matthew; Situ, Sujian; Zhou, Suizan; Gao, Junmei; Liu, Changpeng; Zhang, Jun; Millman, Alexander J.; Zhang, Tao; Tian, Jianmei; et al.
Highlights: We assessed economic burden of influenza in children <5 in Suzhou from 2011-2017. Cost per illness episode was $161 for outpatient and $1426 for hospitalization. Annual economic burden of influenza among children <5 in Suzhou was $7.4 million. Indirect costs accounted for 22-36% of the total annual economic burden. Influenza in children <5 in Suzhou results in a substantial annual economic burden. Abstract: Background: Data are limited on the economic burden of seasonal influenza in China. We estimated the cost due to influenza illness among children < 5-year-old in Suzhou, China. Methods: This study adopted a societal perspective to estimate direct medical cost, direct non-medical cost, and indirect cost related to lost productivity. Data to calculate costs and rates of three influenza illness outcomes (non-medically attended, outpatient and hospitalization) were collected from prospective community-based cohort studies and hospital-based enhanced laboratory-confirmed influenza surveillance in Suzhou during the 2011/12 to 2016/17 influenza seasons. We used mean cost-per-episode, annual incidence rates of episodes of each outcome, and annual population size to estimate the total annual economic burden of influenza illnesses among children < 5-year-old for Suzhou. All costs were reported in 2017 U.S. dollars. Results: The mean cost-per-episode (standard deviation) was $9.92 (13.26) for non-medically attended influenza, $161.05 (176.98) for influenza outpatient illnesses, and $1425.95 (603.59) for influenza hospitalizations. By applying the annual incidence rates to the population size, we estimated an annual total of 4, 919 episodes of non-medically attended influenza, 21, 994 influenza outpatient, and 2, 633 influenza hospitalization. Total annual economic burden of influenza to society among children < 5-year-old in Suzhou was $7.37 (95% confidence interval, 6.9–7.8) million, with estimated costs for non-medically attended influenza of $49, 000 (46, 000–52, 000), influenza outpatients $3.5 (3.3–3.8) million, and influenza hospitalizations $3.8 (3.6–3.9) million. Among outpatients, the indirect cost was 36.3% ($1.3 million) of total economic burden, accounting for 21, 994 days of lost productivity annually. Among inpatients, the indirect cost was 22.1% ($829, 000), accounting for 18, 431 days of lost productivity annually. Conclusions: Our findings show that influenza in children < 5-year-oldcauses substantial societal economic burden in Suzhou, China. Assessing the potential economic benefit of increasing influenza vaccination coverage in this population is warranted.